LINGKUNGAN SEBAGAI MODEL PENDIDIKAN KARAKTER PEDULI LINGKUNGAN: STUDI KASUS PROGRAM SEDEKAH SAMPAH DI MI MUHAMMADIYAH 8 PELANGWOT, LAMONGAN - Benny Prasetiya; Ahsan Hakim; Khoiriyah (LPPM STAI Muhammadiyah Probolinggo, 2024)
Waste problems in community and school environments are not only related to ecological concerns but also closely connected to the formation of moral awareness, social responsibility, and students’ character. This study aims to analyze how character education can be developed through environmental philanthropy in the waste donation program at MI Muhammadiyah 8 Pelangwot, Lamongan. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and supporting questionnaires involving teachers and students who participated in the waste donation program. The data were analyzed using thematic analysis through the stages of data familiarization, coding, theme development, theme review, and interpretation of findings. The results show that the waste donation program originated from the initiative of Pemuda Muhammadiyah in Pelangwot Village as a response to post-Eid al-Fitr waste problems, later gaining community support and becoming integrated into the madrasah’s regular program. This program contributes to the formation of environmentally caring character through the habituation of bringing waste from home every Friday, school cleaning duties, student involvement in waste collection, and the interpretation of waste as a medium of charity. In addition to supporting school finances and cross-subsidies for students from low-income families, the program also serves as a medium of educational communication that connects ecological, social, and religious values. This study confirms that environmental philanthropy can serve as a contextual, participatory, and applicable model of character education for Islamic elementary schools.